2020
DOI: 10.2337/db19-0770
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Against an Important Role of Plasma Insulin and Glucagon Concentrations in the Increase in EGP Caused by SGLT2 Inhibitors

Abstract: Sodium-glucose cotransport 2 inhibitors (SGLT2i) lower plasma glucose but stimulate endogenous glucose production (EGP). The current study examined the effect of dapagliflozin on EGP while clamping plasma glucose, insulin, and glucagon concentrations at their fasting level. Thirty-eight patients with type 2 diabetes received an 8-h measurement of EGP ([3-3 H]-glucose) on three occasions. After a 3-h tracer equilibration, subjects received 1) dapagliflozin 10 mg (n 5 26) or placebo (n 5 12); 2) repeat EGP measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 17 publications
5
32
1
Order By: Relevance
“…Of note, while the SGLT2i-induced increase in the glucagon/insulin ratio likely contributes to enhanced EGP, it is probably not the only mechanism. This is supported by a recent study showing increased dapagliflozin-induced EGP in humans in conditions in which glucagon and insulin secretions were clamped at basal levels by somatostatin [ 52 ]. There is also an ingrained belief that glucagon exerts strong ketogenic activities, particularly during fasting and insulinopenic conditions.…”
Section: Resultssupporting
confidence: 57%
“…Of note, while the SGLT2i-induced increase in the glucagon/insulin ratio likely contributes to enhanced EGP, it is probably not the only mechanism. This is supported by a recent study showing increased dapagliflozin-induced EGP in humans in conditions in which glucagon and insulin secretions were clamped at basal levels by somatostatin [ 52 ]. There is also an ingrained belief that glucagon exerts strong ketogenic activities, particularly during fasting and insulinopenic conditions.…”
Section: Resultssupporting
confidence: 57%
“…These data suggest that increased plasma glucagon concentrations could contribute to increased rates of gluconeogenesis by stimulating intrahepatic lipolysis (57) in this setting. However, a recent study in which subjects were treated with somatostatin to inhibit pancreatic islet hormone secretion of insulin and glucagon, and given an intravenous infusion of replacement basal insulin and glucagon demonstrated an insulin-and glucagon-independent effect of dapagliflozin to increase EGP in humans with T2D (97). In contrast, either blocking catecholamine and corticosterone action, or saline infusion to prevent dehydration, fully abrogated the effect of dapagliflozin to increase EGP in rats, despite a lack of any difference in plasma glucagon concentrations (53).…”
Section: Wat Lipolysis and Sglt2 Inhibitor-induced Euglycemic Ketoacimentioning
confidence: 99%
“…Nevertheless, the present study showed that EGP levels in each condition seemed to be steady at approximately 180 minutes after SGLT2 inhibitor administration, which is a similar result to a previous study showing that EGP was mostly constant from 180 to 300 minutes after SGLT2 inhibitor administration with isoglycaemic and non-isoglycaemic conditions. 10 Finally, we evaluated changes in metabolite and hormone levels between 0 and 180 minutes. However, we cannot exclude the possibility that slight but chronic changes in metabolite and hormone levels (eg, glucagon, NEFA and 3-hydroxybutyric acids) might contribute to EGP change during this period.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, its mechanism has not yet been elucidated. Very recently, Alatrach et al 10 assessed whether EGP elevation after dapagliflozin administration could occur during isoglycaemic or pancreatic clamp conditions in type 2 diabetes. They showed that administration of dapagliflozin led to higher EGP compared with placebo during both isoglycaemic and pancreatic clamp conditions, and concluded that the dapagliflozin-induced increase in EGP cannot be explained by increased plasma glucagon levels or decreased plasma insulin or glucose concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation